Rational use of immunoglobulins (IVIgs and SCIgs) in secondary antibody deficiencies (Swiss Medical Weekly, 2024)
Immunoglobulins for intravenous use (IVIgs) and subcutaneous use (SCIgs) can prevent recurrent and severe infections in patients with secondary antibody deficiencies that are frequently linked to haematological/oncological malignancies as well as other clinical conditions and their respective treatments. Even so, as IVIgs and SCIgs are costly and their supply is limited, their clinical use must be optimised. The aim of this position paper is to provide structured practical guidance on the optimal use of IVIgs and SCIgs in secondary antibody deficiencies, particularly in haematological and oncological practice.The authors agree that the occurrence of severe infections is a prerequisite for the use of IVIgs. Serum IgG levels in general as well as IgG subclass levels can be additional indicators of whether a patient could benefit from IVIgs. Responsiveness to vaccines can help to identify immunodeficiency. Patients with chronic lymphocytic leukaemia or multiple myeloma who are receiving respective treatment, especially B-cell depletion therapy, but also some patients with autoimmune diseases are prone to antibody deficiencies and need IVIgs. For the optimal use of IVIgs and to maximise their potential benefit, the indication must be individually assessed for each patient. As a primary treatment goal, the authors define a sufficient prophylaxis of severe infections, which can be supported by normalising IgG levels. If the initiated treatment is insufficient or linked to intolerable adverse reactions, switching the product within the class of IVIgs or changing to a different batch of the same product can be considered. Pausing treatment can also be considered if there are no infections, which happens more frequently in summer, but treatment needs to be resumed once infections return.These structured recommendations for IVIg treatment in patients with secondary antibody deficiency may provide guidance for clinical practice and therefore help to allocate IVIgs to those who will benefit the most, without overusing valuable resources.